2015
DOI: 10.1007/s11033-015-3856-z
|View full text |Cite
|
Sign up to set email alerts
|

Multifactor dimensionality reduction analysis to elucidate the cross-talk between one-carbon and xenobiotic metabolic pathways in multi-disease models

Abstract: Putatively functional polymorphisms of one-carbon and xenobiotic metabolic pathways influence susceptibility for wide spectrum of diseases. The current study was aimed to explore gene-gene interactions among these two metabolic pathways in four diseases i.e. breast cancer, systemic lupus erythematosus (SLE), coronary artery disease (CAD) and Parkinson's disease (PD). Multifactor dimensionality reduction analysis was carried out on four case-control datasets. Cross-talk was observed between one-carbon and xenob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
(41 reference statements)
0
4
0
1
Order By: Relevance
“…Still, recent meta-analyses reported a COMT association with AD among Asians but not Caucasians [45] Autoimmune disease COMT's role in limiting the damaging effects of oxidative and emotional stress make its potential role in the etiology of auto-immune diseases plausible. Studies in psoriasis, narcolepsy and systemic lupus erythematosus suggest a link between COMT and autoimmune diseases [46][47] Cardiometabolic disease…”
Section: Deliriummentioning
confidence: 99%
See 1 more Smart Citation
“…Still, recent meta-analyses reported a COMT association with AD among Asians but not Caucasians [45] Autoimmune disease COMT's role in limiting the damaging effects of oxidative and emotional stress make its potential role in the etiology of auto-immune diseases plausible. Studies in psoriasis, narcolepsy and systemic lupus erythematosus suggest a link between COMT and autoimmune diseases [46][47] Cardiometabolic disease…”
Section: Deliriummentioning
confidence: 99%
“…COMT's role in limiting the damaging effects of oxidative and emotional stress also make its potential role in the etiology of auto-immune diseases plausible [46]. Studies in psoriasis [67], narcolepsy [68], and systemic lupus erythematosus [47,69] support this hypothesis, but more work needs to be done in this area.…”
Section: Parkinson Disease Ad and Other Diseasesmentioning
confidence: 99%
“…Our previous study underlines the capacity of the SHMT C1420T polymorphism being able to directly reduce breast cancer risk. [ 14 , 38 ]. The study found risk reduction for the SHMT 1420TT genotype in malignant lymphomas [ 39 ], adult acute lymphocytic leukemia [ 40 ], and also in a wide spectrum of diseases including Parkinson’s disease (PD), coronary artery disease (CAD) and systemic lupus erythematosus (SLE) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 , 38 ]. The study found risk reduction for the SHMT 1420TT genotype in malignant lymphomas [ 39 ], adult acute lymphocytic leukemia [ 40 ], and also in a wide spectrum of diseases including Parkinson’s disease (PD), coronary artery disease (CAD) and systemic lupus erythematosus (SLE) [ 38 ]. These suggested that the reduction of DNA damage in the SHMT 1420TT genotype might be the main reason for the risk reduction of different cancers and a wide spectrum of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…метод MDR активно используется для описания взаимодействий неаллельных генов для различных мультифакториальных патологий: рмЖ [9,15,24], рак легкого [16,19], диабет [26,31], артериальная гипертензия [10,14] и др.…”
unclassified